Comparative proteomic and clinicopathological analysis of breast adenoid cystic carcinoma and basal-like triple-negative breast cancer - Yao, Qian; Hou, Wei; Chen, Junbing; Bai, Yanhua; Long, Mengping; Huang, Xiaozheng; Zhao, Chen; Zhou, Lixin; Niu, Dongfeng (Frontiers in Medicine, 2022)
Background: Adenoid cystic carcinoma (ACC) is a rare type of triple-negative breast cancer that has an indolent clinical behavior. Given the substantial overlapping morphologic, immunohistochemical and molecular features with other triple-negative breast cancer with basal-like (BL-TNBC), accurate diagnosis of ACC is crucial for appropriate clinical management. The integrative analysis of the proteome and clinicopathological characteristics may help to distinguish these two neoplasms and provide deep understanding on biological behaviors and potential target-therapy of ACC. Methods: We applied mass spectrometry-based quantitative proteomics to analyze the protein expression in paired tumor and adjacent normal breast tissue of five ACC and five BL-TNBC. Bioinformatic analyses and the clinicopathological information including histologic features, immunohistochemistry and FISH were also conducted to get the comprehensive information. Results: A total of 307 differentially expressed proteins (DEPs) were identified between ACC and BL-TNBC. Clustering analysis of DEPs clearly separated ACC from BL-TNBC. GSEA found down-regulation of the immune response of ACC compared to BL-TNBC which consistent with the negative PD-L1 expression of ACC. Vesicle-mediated transport was also inhibited while ECM organization was enriched in ACC. The top upregulated protein in DEPs were ITGB4 and VCAN. Moreover, with comparison to normal breast tissue, ACC showed elevated ribosome biogenesis and RNA splicing activity. Conclusions: This study provide evidence that ACC harbors substantially different proteomic profile compared with BL-TNBC and promote our understanding in the molecular mechanisms and biological processes of ACC, which might be useful for differential diagnosis and anticancer strategy.